(3eLQO ebGdGJ CHj GdMSf GdCTYQis - (3eMeO Hf GdMSf Hf GdeHGQcs
(3ChdgG (B:s
(3GdMeO ddg GhdkG hGNQkG CeG HYO abO hbaJ Ydi eG SCdJe Edi Gdhbha Ydi GUhd ePGgH TjNfG CHj GdMSf Ydi Hf GSeGYjd GdGTYQi GdaUd GdChd ai GHGfI ePgHg ai eYfi GdYde hMOg s
(3BNQgG (B:s
(3hEfeG LQjfG ag Ydi gPG GdefGd GdPi QSefGg dc aGYdeg Ef TGA Gddg hMOg gPG BNQ GdcJGH hGdMeO ddg GhdkG hCNQkG hUdi Gddg Ydi SjOfG eMeO GdfHi hidg hSde cKjQkG s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YGQa MceJ HGdeOjfI GdefhQI (B((3JhMjO (B232) s
Keywords: (3GdJhMjO hGdedd hGdfMds